2019
DOI: 10.1038/s41564-019-0403-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural dynamics of bacteriophage P22 infection initiation revealed by cryo-electron tomography

Abstract: SUMMARY For successful infection, bacteriophages must overcome multiple barriers to transport the genome and proteins across the bacterial cell envelope. We use cryo-electron tomography to study infection initiation of phage P22 in Salmonella enterica sv. Typhimurium, revealing how a channel forms to allow genome translocation into the cytoplasm. Our results show free phages initially attaching obliquely to the cell through interactions between the O antigen and two of the six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 59 publications
(93 reference statements)
1
77
0
1
Order By: Relevance
“…Members of the Podoviridae family, such as E. coli phage T7, have very short and non-contractile tails. A tube-like extension of the tail that penetrates both cell membranes was observed to be essential for genome delivery into the host 29 .…”
Section: Tailed Bacteriophagesmentioning
confidence: 99%
“…Members of the Podoviridae family, such as E. coli phage T7, have very short and non-contractile tails. A tube-like extension of the tail that penetrates both cell membranes was observed to be essential for genome delivery into the host 29 .…”
Section: Tailed Bacteriophagesmentioning
confidence: 99%
“…Binding the multivalent TSP to the multivalent sensor surface mimics the situation during phage infection, where the TSP as part of the phage tail has to bind perpendicular to the bacterial cell surface. Although the also perpendicularly protruding O‐antigen chains would suggest a mainly parallel orientation of TSP and polysaccharide chains, cryoelectron tomography analyses showed that whole phage particles bound obliquely to the cell surface . Therefore, an SPR surface‐immobilized polysaccharide that might contain also surface‐parallel regions mimics this situation, as periodate treatment of the polysaccharide might interfere with its fully perpendicular attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Althought he also perpendicularly protruding O-antigen chains would suggest a mainly parallel orientation of TSP and polysaccharide chains, cryoelectron tomography analysess howedt hat whole phage particles bound obliquelyt ot he cell surface. [70] Therefore, an SPR surface-immobilized polysaccharide that might contain also surface-parallel regions mimics this situation, as periodate treatment of the polysaccharide might interfere with its fully perpendicular attachment. Here, interaction with more than one glycan binding site per TSP would then require a6 0 8 rotation aroundt he symmetry axis and result in an energetic penalty.I ndeed, the negative cooperativity found in the Scatchard plot might point to this unfavourable surface binding where two sites on one TSP must bind simultaneously.M odelst hat are more sophisticated should be therefore used that take into account the reactionv olumea nd ap robability factor for the multivalent bindinge vent.…”
Section: Discussionmentioning
confidence: 99%